Diagonal replication technique for high data availability in distributed database systems - Nathrah Bakar (Fakulti Sains dan Teknologi, 2011)
In a distributed database systems environment, database replication is the most widely used concept to offer high data availability, fault tolerance mechanism, and enhanced system performance. In such system, a mechanism is required to maintain the consistency of the replicated data, determine the number of replication required and where the replicated are to be stored. This is largely due to the limitation in storage capacity.